ffects of cations, anions and H+ concentration of acidic ionic liquids on the valorization of polysaccharides into furfural - Matsagar, Babasaheb M.; Dhepe, Paresh L. (New Journal of Chemistry, 2017)
The valorization of hemicellulose into valuable chemicals, such as C5 sugars and furfural, in a one-pot fashion is crucial. In this work, acidic ionic liquids in the presence of water showed high yields of C5 sugars (>80%) with >99% conversion of hemicelluloses at 160 degrees C. With a water + toluene biphasic solvent system, within 4 h, an 85% furfural yield was obtained directly from hemicellulose in a one-pot fashion using a catalytic amount of 1-methyl-3-(3-sulfopropyl)-imidazolium hydrogen sulfate. It was seen that Bronsted acidic ionic liquids (BAILs) perform better than solid acid [Faujasite and Mordenite zeolites; ion exchange resin, Amberlyst-15] and mineral catalysts [HCl and H2SO4]. The higher activity of BAILs compared to solid acids and mineral acids was correlated to the Hammett acidity function (Ho) and ion-dipole type of interactions. The catalysts were characterized using NMR (H-1 and C-13), elemental analysis and TGA to confirm that they were stable under reaction conditions and were thus recyclable.